Evaluasi Efektivitas Penggunaan Chemical Pour Point Depressant 150 ppm Terhadap Crude Oil dari 3 Sampel Sumur Lapangan Sangatta - Alfin Rezeki Effendi; Baiq Maulinda Ulfah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The formation of wax crystals in crude oil at low temperatures can increase viscosity and block flow, making the use of chemical pour point depressants (PPD) necessary. This study aimed to evaluate the effectiveness of PPD at a concentration of 150 ppm in lowering the pour point and to analyze the relationship between crude oil characteristics and pour point values. Testing was carried out on three crude oil samples from the Sangatta Field using standards ATM D1298 (API Gravity), ASTM D4007 (BSS&W), ASTM D445 (viscosity), and ASTM D97 (pour point). The results showed that samples with lower API Gravity, and higher viscosity and BS&W, had higher pour points. Adding 150 ppm lowered the pour point of sample XY from 23°C to 11°C, YY from 24°C to 13°C, and ZY from 26°C to 19°C. Using 150 ppm PPD is recommended as an option to improve crude oil flow under low temperature conditions.